Fulfillment of Family Maintenance by Minors Due to Parents with Prisoner Status from the Perspective of Islamic Family Law - L.Man, Yovenska (Universitas Islam Negeri Raden Intan Lampung, 2026)
The phenomenon of minors becoming family breadwinners due to their parents being imprisoned reflects a shift in family structure that affects children's rights and the implementation of maintenance obligations in Islamic Family Law. This study aims to analyze the causal factors, the impact on the fulfillment of children's rights, and the legal position of child breadwinners from the perspective of Islamic Family Law. The research employed a qualitative field research design using a socio-juridical approach. Data were analyzed through the perspectives of family resilience theory, role theory, and Maqāṣid al-Sharī’ah, applying data reduction, presentation, and conclusion-drawing techniques. The findings indicate that children's involvement in economic activities represents a family adaptation strategy to the loss of the primary breadwinner, yet it adversely affects their rights to education, protection, and development. From the perspective of Islamic Family Law, such circumstances do not transfer maintenance obligations to children but reaffirm the collective responsibility of families, communities, and the state. The study recommends strengthening family protection policies, economic empowerment programs, and social assistance to safeguard children's rights in vulnerable families.